Robotic lateral pelvic lymph node dissection after chemoradiation for rectal cancer: a Western perspective. (21st September 2020) - Peacock, O.; Limvorapitak, T.; Bednarski, B. K.; Kaur, H.; Taggart, M. W.; Dasari, A.; Holliday, E. B.; Minsky, B. D.; You, Y. N.; Chang, G. J.
Abstract: Aim: There are limited outcome data for lateral pelvic lymph node dissection (LPLND) following neoadjuvant chemoradiotherapy (nCRT), particularly in the West. Our aim was to evaluate the short‐term perioperative and oncological outcomes of robotic LPLND at a single cancer centre. Method: A retrospective analysis of a prospective database of consecutive patients undergoing robotic LPLND for rectal cancer between November 2012 and February 2020 was performed. The main outcomes were short‐term perioperative and oncological outcomes. Major morbidity was defined as Clavien–Dindo grade 3 or above. Results: Forty patients underwent robotic LPLND during the study period. The mean age was 54 years (SD ± 15 years) and 13 (31.0%) were female. The median body mass index was 28.6 kg/m 2 (IQR 25.5–32.6 kg/m 2 ). Neoadjuvant CRT was performed in all patients. Resection of the primary rectal cancer and concurrent LPLND occurred in 36 (90.0%) patients, whilst the remaining 4 (10.0%) patients had subsequent LPLND after prior rectal resection. The median operating time was 420 min (IQR 313–540 min), estimated blood loss was 150 ml (IQR 55–200 ml) and length of hospital stay was 4 days (IQR 3–6 days). The major morbidity rate was 10.0% ( n = 4). The median lymph node harvest from the LPLND was 6 (IQR 3–9) and 13 (32.5%) patients had one or more positive LPLNs. The median follow‐up was 16 months (IQR 5–33 months), with 1 (2.5%) local central recurrence and 7 (17.5%) patients developing distant disease, resulting in 3 (7.5%) deaths. Conclusion: Robotic LPLND for rectal cancer can be performed in Western patients to completely resect extra‐mesorectal LPLNs and is associated with acceptable perioperative morbidity.